Residue levels and health risk of pesticide residues in bell pepper in Shandong. Issue 9 (2nd September 2019) - Chu, Zunhua; Zhuang, Maoqiang; Li, Suyun; Xiao, Peirui; Li, Ming; Liu, Danru; Zhou, Jingyang; Chen, Jindong; Zhao, Jinshan
ABSTRACT: The purpose of this study was to investigate pesticide residues in bell peppers from Shandong Province, China. A total of 299 samples were collected from 17 cities in 2016. The concentrations of 26 pesticide residues were determined by gas chromatography with mass spectrometry (GC–MS). The results showed that there were 25 pesticides (15 OPs, 7 PYs, 3 CBs) found in 86 bell pepper samples, and the total number of positives was 120. The total frequency was 28.76%. The detection frequency for OPs, PYs and CBs was 16.39%, 12.37% and 3.01%, respectively. The most frequently detected pesticide was bifenthrin, with the frequency of 5.02%. 5.35% of samples contained pesticide residues above the maximum residue limits (MRLs) set by China. 7.36% of samples contained more than one pesticide. The values of %ADI were below 100, while the %ARfD of carbofuran and methidathion exceeded 100 for children. The cumulative risk was highest for OPs. From the public health point of view, the levels of pesticide residues in bell peppers do not pose a serious health risk to adults, but the acute health risk to children should be paid more attention. Graphical Abstract: